2015
DOI: 10.1111/wrr.12244
|View full text |Cite
|
Sign up to set email alerts
|

A study on the ability of quaternary ammonium groups attached to a polyurethane foam wound dressing to inhibit bacterial attachment and biofilm formation

Abstract: Bacterial infection of acute and chronic wounds impedes wound healing significantly. Part of this impediment is the ability of bacterial pathogens to grow in wound dressings. In this study, we examined the effectiveness of a polyurethane (PU) foam wound dressings coated with poly diallyl-dimethylammonium chloride (pDADMAC-PU) to inhibit the growth and biofilm development by three main wound pathogens, Staphylococcus aureus, Pseudomonas aeruginosa, and Acinetobacter baumannii, within the wound dressing. pDADMAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 37 publications
(81 reference statements)
1
22
0
Order By: Relevance
“…Then, the biofilms were examined by CLSM using a Nikon A1+/AIR+ Confocal Microscope (Nikon Inc., Melville, NY). NIS‐Elements 2.2 software (Nikon) was used to generate three‐dimensional biofilm images as described previously . All experiments were conducted in at least triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the biofilms were examined by CLSM using a Nikon A1+/AIR+ Confocal Microscope (Nikon Inc., Melville, NY). NIS‐Elements 2.2 software (Nikon) was used to generate three‐dimensional biofilm images as described previously . All experiments were conducted in at least triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…Attempts have also been made to incorporate QA groups into wound dressing materials. Attachment of QA groups to a polyurethane foam wound dressing [220] resulted in inhibition of biofilm development of three major wound pathogens (S. aureus, P. aeruginosa and Acinetobacter baumannii) both within the wound and in the wound dressing. Wound healing requires a moist and warm environment, and dressing materials with good air permeability and moisture absorption are desirable.…”
Section: Sutures and Wound Dressingsmentioning
confidence: 99%
“…Previous studies on the antimicrobial properties of a non‐leaching urethane wound‐dressing material that has long chain polymers with high densities of quaternary amines (pDADMAC) attached to its surface showed that they were effective in controlling bacterial biofilms when studied in vitro . The present study was carried out to see whether the same wound‐dressing material can play an active role in the treatment process of a wound in vivo using a mouse wound model.…”
Section: Introductionmentioning
confidence: 95%